Iconicity and Deconstruction: the Prose by Vladimir Nabokov and the 20th Century Post-Modernist Philosophy - N. F. Shcherbak (Дискурс)
Introduction. This research aims at analyzing the novel by Vladimir Nabokov Transparent Things (1972) from the perspective of post-modernist philosophy. By post-modernist philosophy I mean the post-structural view of the sign theory, that focuses on iconicity, symbolic and iconic nature of the sign, the сoncept of deconstruction, the concept of rhizome, the concept of silence, the concept of différance (as stated by Derrida), the concept of difference and repetition introduced by G. Deleuze. This philosophy is linked to a more general view expressed, for instance, by Derrida (in his work the Gift of Death (Donner la mort)). The main innovative element of this research, therefore, is to study the prose by Nabokov as an example of post-modernist writing simultaneously applying the views and concepts introduced by cognitive linguistics, literary critics and post-modern writers like J. Derrida, U. Eco, R. Barthes.Methodology and sources. The research method used is semantic and structural analysis of the novel by Nabokov Transparent Things. Its main tool is the use of ideas introduced by French poststructuralists regarding the theory of sign, the symbolic nature of language, study of multiple meanings generated by a word in the process of its use and decoding.Results and discussion. The results of this research allow to outline main tendencies in the development of the 20th century narrative. It adheres to the general law of multi-level structure of the novel, play of words and sounds, which corresponds to the general view of difference (as coined by Derrida), deconstruction, rhizome, iconicity of sign. The rhizomorphic structure of the novel at the same time is mirror-like, which allows to apply the difference-repetition dichotomy put forward by G. Deleuze. If the micro-structure of Nabokov’s texts allows to make generalization about the author’s use of language, its macro-structure reveals deeper philosophical notions, implying that the death of the character in the novel leads to the study of the transcendental, or ”the Other” in psychoanalytical terms, thus putting the plot on a different scale of values. The view of language and its structure in its relation to the notion of transparency, allows to see the sign in a Heideggerian way, as bearing the replica of the world, having more in itself about the world, than anything else.Conclusion. The novel Transparent Things by Nabokov falls into the category of similar novels in which the author develops symbolic language and explores its potential, following the general pattern and establishing the rules of narrative construction in postmodern tradition.